ANALISIS KEBUTUHAN ILUMINASI AUDITORIUM MOKODOMPIT UNIVERSITAS HALUOLEO - Gamel Abdel Nasser (Universitas Halu Oleo, 2008)
Target expected from this research is to determine the correct illumination as same as to standardization and to determine the required lamp dot amount. Method used is Literature study, that is by conducting book study of related to calculation analysis, that is conduct the calculation analysis of pursuant to data obtained from picture of planning of auditorium building. Conclusion and result obtained by that factor influencing illumination calculation of a building is high of assembling shop of lamp to area enlightened the, used lamp type, angle of deflection lamp, sum up the used lamp, wide of area surface enlightened. Considering the level of illumination standard for the building of auditorium is 1000 Lux, to analyze the level of illumination used at Mokodompit Auditorium of Haluoleo University can be told extravagant Key words: Auditorium Unhalu, iluminasi, metode lumen